Workplace health promotion interventions for nurses in Germany: a systematic review based on the RE-AIM framework - Andrea Schaller; Madeleine Gernert; Teresa Klas; Martin Lange (BMC, 2022)
Abstract Background The German health care system is faced with a serious shortage of nurses. This is associated, amongst other things, with difficult working conditions and work-related health burdens. Workplace health promotion (WHP) is considered a promising approach to promote the health of nurses. The present review aims to give an overview on existing interventions in different nursing settings (acute care hospitals, long-term care (LTC) facilities and home-based long-term care) in Germany. Methods A systematic literature search was conducted in PubMed and PubPsych. Studies were included if published after 2010 and provided data of intervention studies on workplace health promotion among nurses in Germany (RCTs, non-RCTs, non-controlled intervention studies and pilot studies). The setting in which the study was conducted (acute medical care hospital, inpatient LTC facilities, home-based LTC, cross-setting) as well as the health issue assessed (physical health, mental health and/or violence experience) were extracted. The intervention was reported against the background of the quality criteria for prevention measures of the statutory health insurers in Germany. The results of the studies were presented according to the RE-AIM framework. Results Eleven studies on WHP for nurses were included, whereof seven studies were conducted in acute medical care hospitals and four in LTC facilities. No study reported results on WHP for nurses working in the setting of home-based LTC. Most studies aimed at improving mental health. The intervention contents and forms of implementation were heterogeneous. According to the RE-AIM criteria, the reporting of most studies showed several limitations, especially a lack of reporting on Implementation and Adoption. Most studies showed no statistically significant effect on the respective outcomes (Effectiveness). Four studies reported results on Maintenance indicating a sustained effectiveness. Conclusion Despite the high relevance for health promotion for nurses, our review showed a striking lack of intervention studies in this field. From this we derive a high need of tailored interventions, taking into account the setting-specific development, implementation of WHP interventions for nurses. With regard to the evaluation, the RE-AIM criteria should be taken more into account in order to meet the requirements of evaluating complex interventions and thus contribute to evidence development of WHP in nursing. In terms of content, the topic of violence prevention and dealing with experiences of violence should also be taken into account. Regarding the settings, the working conditions and health burdens in LTC facilities, home-based LTC and acute medical hospitals must be considered. Trial registration PROSPERO registration number: CRD42021231891